PENGEMBANGAN USAHA PASAMAN PIZZA MELALUI ANALISIS SWOT - Yuliza, Mai; Muchia Desda, Mia (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2021)
One of the growing businesses in West Pasaman is the Pizza business "Pasaman Pizza" where this business starts from the ambition to open a business with great profits, acceptable to the surrounding community and can develop to include outside West Pasaman. For this reason, "Pasaman Pizza" as a business in the culinary field that provides pizza variants in accordance with consumer interests. The purpose of this study is to use a SWOT analysis to determine the development of the Pasaman Pizza business. The data was analyzed using a qualitative descriptive method called SWOT analysis. According to the findings, Pasaman Pizza should improve its social media marketing efforts, open new branches to expand its business, and continue to prioritize taste, good customer service, and innovative marketing. Given Pasaman Pizza's strengths and opportunities, it's possible that, despite its flaws and threats, Pasaman Pizza will be an excellent business prospect to run and develop.